PERANAN ASAS GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN DAN PENGEMBANGAN DI INDUSTRI PERBANKAN - Arief Bimantara, Gustav Satria; Ariawan, I Gusti Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013)
The implementation of principles Good Coorporate Governance for the bank’s internal improvement has been sure of giving the strong fundamentally for the prudential and profesionality. The Implementation of principles Good Coorporate Governance will give the possibility of self regulatory that controlling the behavior of management and all of staf according to professional principles, business ethic, accountability, and transparency. The Implementation of principles Good Coorporate Governance will be a fundamental aspect for developing of business and institutions will be a fundamental aspect for banking industry.
Keywords: Good Corporate Governance, Developing, Banking Institutions